2022
DOI: 10.2298/tsci210528263h
|View full text |Cite
|
Sign up to set email alerts
|

Design and verification of ultra-high temperature lithium heat pipe based experimental facility

Abstract: Lithium heat pipe has broad applications in heat pipe cooled reactors and hypersonic vehicles due to its ultra-high working temperature which is around 1700 K. In this paper, a lithium heat pipe based experimental facility has been designed to test the heat transfer performance of the lithium heat pipe. A simplified mathematical model of heat pipe has been implemented into a CFD approach, which is used to verify the design of lithium heat pipe and its experimental facility. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…More recently, several research projects have been adopting a more practical approach, coupling numerical investigations with extensive experimental campaigns. Tokuda and Inoue [36] investigated the thermal performance of an oscillating heat pipe with sodium as a working fluid, while Hu et al [22] designed a lithium heat pipe-based experimental facility to test the heat transfer performance of a lithium heat pipe. The work of Hu et al is very interesting because the description of the experimental setup is complemented with a simplified mathematical model implemented into a CFD approach, which is used to verify the design of the lithium heat pipe and its experimental facility.…”
Section: Recent Studies Of Heat Pipesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, several research projects have been adopting a more practical approach, coupling numerical investigations with extensive experimental campaigns. Tokuda and Inoue [36] investigated the thermal performance of an oscillating heat pipe with sodium as a working fluid, while Hu et al [22] designed a lithium heat pipe-based experimental facility to test the heat transfer performance of a lithium heat pipe. The work of Hu et al is very interesting because the description of the experimental setup is complemented with a simplified mathematical model implemented into a CFD approach, which is used to verify the design of the lithium heat pipe and its experimental facility.…”
Section: Recent Studies Of Heat Pipesmentioning
confidence: 99%
“…More recently, efforts to create new extraterrestrial outposts or reach farther space destinations are pushing researchers to develop space nuclear reactors. These systems will require extreme cooling capabilities, which might be granted by ultra-high-temperature heat pipes [22].…”
Section: Introduction 1thermal Management Challenges In the Aerospace...mentioning
confidence: 99%
“…A startup scheme based on the analysis of transient thermohydraulic behavior during cold start-up was proposed for a three-stage HPCR with high safety. Hu et al (2022) developed a network code in Python specifically for ultrahigh temperature lithium HPs. The study found that increasing the wall thickness and wick thickness of a HP leaded to an increase in the transition time.…”
Section: Startup Characteristicmentioning
confidence: 99%